Estimation of separation quality and costs of heat in rectification processes - M. K. Zakharov; Mohand Abbasy; E. N. Zvereva (Тонкие химические технологии)
Different criteria for the quantification of the quality of binary mixtures separation by rectification were compared. The best criterion for the binary mixtures was selected. The unit energy costs in the case of rectification of binary mixtures with different separabilities and the compositions of the initial mixture were found. It is shown that due to the internal energy saving in the processes of rectification the average separability of mixtures (40 to 60%) the unit cost of heat in the reboiler is close to the latent heat of vaporization of the mixtures. In this case the purity of shared components is 98%.